Self-evolved hydrogen peroxide boosts photothermal-promoted tumor-specific nanocatalytic therapy. Issue 22 (13th May 2019) - Gao, Shanshan; Lu, Xiangyu; Zhu, Piao; Lin, Han; Yu, Luodan; Yao, Heliang; Wei, Chenyang; Chen, Yu; Shi, Jianlin
Abstract : Highly efficient nanocatalytic tumor therapy has been achieved by in situ self-supplied H2 O2 -triggered and photothermally-promoted Fenton reaction by the rational design of two-dimensional composite nanoreactors. Abstract : The emerging nanocatalytic tumor therapy such as chemodynamic therapy (CDT) converts less harmful hydrogen peroxide (H2 O2 ) into highly toxic hydroxyl radicals (˙OH) via metal ion-mediated catalytic Fenton chemistry, which has motivated extensive research interest due to the high specificity of the nanocatalytic reactions to the tumor microenvironment (TME) and minimized side effects. However, traditional CDT substantially suffers from the insufficiency of intratumoral H2 O2 for inducing a satisfactory therapeutic efficacy. In this work, we report on a photothermally-promoted Fenton reaction triggered by self-supplied H2 O2, based on the constructed two-dimensional (2D) multifunctional therapeutic Nb2 C–IO–CaO2 nanoreactors with enhanced therapeutic efficacy and therapeutic biosafety. These Nb2 C–IO–CaO2 nanoreactors employ calcium peroxide (CaO2 ) as a potent H2 O2 supplier to sustain the iron oxide (IO) nanoparticle-mediated catalytic Fenton reaction, and to liberate highly toxic ˙OH for inducing tumor-cell apoptosis. Meanwhile, the intratumoral ˙OH production was further promoted by the photothermal effect of the Nb2 C–IO–CaO2 nanoreactors under near infrared irradiation at the second biowindow. Extensive in vitro and in vivo evaluations have demonstrated significantly enhanced reactive oxygen species (ROS) production and an outstanding photothermal effect based on these Nb2 C–IO–CaO2 nanoreactors, which synergistically lead to elevated therapeutic efficacy. Therefore, this work not only exhibits a promising prospect for reforming the TME to achieve enhanced Fenton reactivity for CDT by elaborately designed nanomaterials with multifunctionality, but also provides novel efficient cancer-therapeutic modalities with simultaneous high therapeutic efficacy and low side effects.